Materials Development for High Efficiency Superconducting Nanowire Single-Photon Detectors. Issue 1807 (2015) - Lita, A.E.; Verma, V.B.; Horansky, R. D.; Shainline, J.M.; Mirin, R.P.; Nam, S.
ABSTRACT: Superconducting nanowire single-photon detectors (SNSPDs) based on ultra-thin films have become the preferred technology for applications that require high efficiency single-photon detectors with high speed, high timing resolution, and low dark count rates at near-infrared wavelengths. Since demonstration of the first SNSPD using NbN thin films, an increasingly larger number of materials are being explored. We investigate amorphous thin film alloys of MoSi, MoGe, and WRe with the goal of optimizing SNSPDs for higher operating temperature, high efficiency and high speed. To explore material adequacy for SNSPDs, we have measured superconducting transition temperature ( T c ) as a function of film thickness and sheet resistance, as well as critical current densities. In this paper we present our results comparing these materials to WSi, another amorphous material widely used for SNSPD devices.